THE NATIONAL SPACE AND BORDERS AS VARIABLES IN INTERNATIONAL RELATIONS AND FOREIGN POLICY: THE SPECIFICITY OF TERRITORIAL NEGOTIATIONS - Peruana de Derecho Internacional, Sociedad (2020)
Territoriality is an essential variable of relationshipsinternational and foreign policy. The territory, including its projectionmaritime, condition and influence relations between States. Thepower, strategic, political, economic-commercial relations and everythingtype of international interaction refers directly or indirectly to theNational space of the States. In this perspective, the dynamics ofcooperation and conflict they have in the territory and their material expressionsand legal, such as sovereignty, limits, borders, its areas of actionmore linked to national interests, conscience and identitynational. Their importance in international action gives them regulationsconstitutional laws that limit and regulate foreign policy decisionsreferred to these permanent national interests. Conflict is aprivileged dynamics of territoriality. Especially in their bondingwith the limits and factors that define national identity. The author analyzesall this problematic and links it to types of interstate conflict andvarious non-jurisdictional dispute settlement mechanisms, withan emphasis on the analytical description of the specificities of the negotiationterritorial.